The China puzzle: Opportunities for accounting research - Suresh Radhakrishnan (China Journal of Accounting Research, 2014)
How can China achieve phenomenal economic growth despite what is considered as "weak" institutions in market-based economies? Xu (2011) provides a framework to understand this puzzle. Specifically, he suggests that China's institutional framework of Regionally Decentralized Authoritarian regime was likely responsible for the phenomenal economic growth despite what is considered "weak" institutions for market-based economies. While recent accounting research provides insights into the relationship between agency issues, and accounting and control systems in the China context, accounting researchers can use the institutional feature of RDAs to provide insights into the role of accounting and control systems in non-market-based settings.
Keywords: 650